Differentiating malignant and benign pleural effusion in patients with lung cancer: an 18F-FDG PET/CT retrospectively study - Zhang, Weishan; Liu, Zhe; Duan, Xiaoyi; Li, Yan; Shen, Cong; Guo, Youmin; Yang, Jian (Frontiers in Oncology, 2023)
Rationale: To explore the clinical role of 18 F-fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT) in differentiating malignant pleural effusion (MPE) from and a benign pleural effusion (BPE) in patients with lung cancer.Methods: Over a 8-year period, we retrospectively reviewed PET/CT data of lung cancer patients with pleural effusion,patients with lung cancer and a pleural effusion, with 237 participants enrolled for analysis. The nature of pleural effusion was confirmed using pleural cytology or biopsy. MPE versus BPE comparison and multiple regression analysis were performed. Receiver operating characteristic (ROC) curve analysis was used for evaluating the diagnostic performance.Results: Of the 237 participants, 170 had MPEs and 67 had BPEs. Compared with BPEs, MPEs had higher pleural SUVmax and thicker pleura and were more common among non-small cell lung cancers, peripheral tumors, and women (p < 0.05). BPEs had larger and higher 18 F-FDG uptake thoracic lymph nodes and more complications of pneumonia (p < 0.05) than MPEs. Multiple regression analysis was used to identify the pleural SUVmax (odds ratio, OR = 38.8), sex (OR = 0.033), and mediastinal lymphoid node size (OR = 0.86) as independent risk factors for MPEs.The sensitivity, specificity, and area under the ROC curve (AUC) in the combined ROC curve analysis by using the three factors were 95.3%, 95.5%, and 0.989, respectively.18 F-FDG PET/CT integrated imaging is an effective non-invasive method for differential diagnosis of MPE in patients with lung cancer. Pleural glycolysis SUVmax combined with thoracic lymph nodes and sex has high diagnostic value.